AOP Report: Inhibition of Chitin Synthase 1 Leading to Increased Mortality in Arthropods. (30th June 2021) - Schmid, Simon; Song, You; Tollefsen, Knut Erik
INTRODUCTION AND BACKGROUND: Arthropods (including insects, crustaceans, and arachnids) rely on the synthesis of chitin to complete their life cycles (Merzendorfer 2011). The highly conserved chitin synthetic process and the absence of this process in vertebrates make it an exploitable target for pest management and veterinary medicines (Merzendorfer 2013; Junquera et al. 2019). Susceptible, nontarget organisms, such as insects and aquatic invertebrates, exposed to chitin synthesis inhibitors may suffer population declines, which may have a negative impact on ecosystems and associated services. Hence, it is important to properly identify, prioritize, and regulate relevant chemicals posing potential hazards to nontarget arthropods. The need for a more cost‐efficient and mechanistic approach in risk assessment has been clearly evident and triggered the development of the adverse outcome pathway (AOP) framework (Ankley et al. 2010). An AOP links a molecular initiating event (MIE) through key events (KEs) to an adverse outcome. The mechanistic understanding of the underlying toxicological processes leading to a regulation‐relevant adverse outcome is necessary for the utilization of new approach methodologies (NAMs) and efficient coverage of wider chemical and taxonomic domains. In the last decade, the AOP framework has gained traction and expanded within the (eco)toxicological research community. However, there exists a lack of mature invertebrate AOPs describing molting defect–associated mortality triggered by direct inhibition of relevant enzymes in the chitin biosynthetic pathway (chitin synthesis inhibitors) or interference with associated endocrine systems by environmental chemicals (endocrine disruptors). Arthropods undergo molting to grow and reproduce (Heming 2018). This process is comprised of the synthesis of a new exoskeleton, followed by the exuviation of the old exoskeleton (Reynolds 1987). The arthropod exoskeleton (cuticle) can be divided into 2 layers, the thin and nonchitinous epicuticle, which is the outermost layer of the cuticle, and the underlying chitinous procuticle. A single layer of epithelial cells is responsible for the synthesis and secretion of both cuticular layers (Neville 1975). The cuticle protects arthropods from predators and desiccation, acts as a physical barrier against pathogens, and allows for locomotion by providing support for muscular function (Vincent and Wegst 2004). Because the procuticle mainly consists of chitin microfibrils embedded in a matrix of cuticular proteins supplemented by lipids and minerals in insects (Muthukrishnan et al. 2012) and crustaceans (Cribb et al. 2009; Nagasawa 2012), chitin is a determinant factor for the appropriate composition of the cuticle and successful molting (Cohen 2001). A detailed overview of the endocrine mechanisms regulating chitin synthesis is given in Supplemental Data, Figure S1. The shedding of the old exoskeleton in insects is mediated by a sequence of distinct muscular contractions, the ecdysis motor program (EMP; Ayali 2009; Song et al. 2017a). Like the expression of chitin synthase isoform 1 (CHS‐1), the expression of peptide hormones regulating the EMP is also controlled by ecdysteroids (Antoniewski et al. 1993; Gagou et al. 2002; Ayali 2009). Cuticular chitin is polymerized from uridine diphosphate‐ N ‐acetylglucosamine (UDP‐GlcNAc) by the transmembrane enzyme CHS‐1, which is localized in the epithelial plasma membrane in insects (Locke and Huie 1979; Binnington 1985; Merzendorfer and Zimoch 2003; Merzendorfer 2006). Because crustaceans are also dependent on the synthesis of chitin, the underlying mechanisms are believed to be similar, although less is known about different CHS isoforms and their localization (Rocha et al. 2012; Qian et al. 2014; Uddowla et al. 2014; Harðardóttir et al. 2019). Disruption of either chitin synthesis or the upstream endocrine pathways can lead to lethal molting disruption (Arakawa et al. 2008; Merzendorfer et al. 2012; Song et al. 2017a, 2017b). In the case of chitin synthesis inhibition, molting disruption can be referred to as "premature molting." If ecdysis cannot be completed because of decreased chitin synthesis, the organism may not successfully molt. Even if ecdysis can be completed on inhibition of chitin synthesis, the organism may not survive because of the poor integrity of the new cuticle. These effects are observed in arthropods following molting, which fail to survive subsequent molts (Arakawa et al. 2008; Chen et al. 2008) or animals being stuck in their exuviae (Wang et al. 2019) and ultimately dying as a result of insufficient food or oxygen intake (Camp et al. 2014; Song et al. 2017a). The term "premature molting" is used to differentiate from the term "incomplete ecdysis, " which describes inhibition of ecdysis on a behavioral level, namely through reduction of the EMP (Song et al. 2017a). The present AOP describes molting‐associated mortality through direct inhibition of the enzyme CHS‐1. It expands the small but increasing number of invertebrate AOPs that have relevance to arthropods, the largest phylum within the animal kingdom (Bar‐On et al. 2018). The development of this AOP will be useful in further research and regulatory initiatives related to assessment of CHS inhibitors and identification of critical knowledge gaps and may suggest new strategies for ecotoxicity testing efforts. Environ Toxicol Chem 2021;40:2112–2120. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.